Treatment of standardised wounds with pure epidermal micrografts generated with an automated device - Bührer, Gregor; Arkudas, Andreas; Horch, Raymund E. (International Wound Journal, 2017)
In this study, we analysed the effects of pure epidermal micrografts generated with an automated device in a standardised human wound model. Epidermal micrografts were harvested using an automated device. Micrografts were then transplanted onto split-skin donor sites. The target area was only partially covered with transplants to create an intra-individual control area. Wounds were evaluated by subjective assessment as well as measurements with combined laser and white light spectroscopy and cutometry. The epidermal graft sites remained completely stable, whereas control sites offered partially unstable and blistering areas. Statistically, no measurable difference in the speed of initial reepithelialisation could be shown. However, there was an increased pliability and softness of the treated areas that correlated with the subjective impression of both investigators and patients. There was a significantly higher relative haemoglobin concentration, measurable in treated and untreated areas at 4 weeks and 6 months. Cutometry showed no differences in skin properties between treated and untreated areas. This study shows an effect of epidermal micrografts in a standardised human wound model and supports the positive impact of keratinocytes on early wound healing as described in literature. Long-term effects of epidermal grafting deserve further studies.
EVALuna2:32837